The resilient Merlot: from global growth to sustainable viticulture and winemaking in the age of climate change - Gridello, Emma; Colautti, Andrea; Pellegrini, Michela; Comi, Giuseppe; Iacumin, Lucilla (Frontiers in Sustainable Food Systems, 2025)
Merlot, a grape variety with a rich history and significant genetic diversity, has become one of the most influential cultivars in the global wine industry. Its adaptability to diverse climates has enabled extensive cultivation in major wine-producing regions, including France, Italy, the United States, Australia, and Chile. This adaptability, combined with its ability to produce consistently high-quality wines, underlines the importance of reviewing and understanding its future potential. Merlot originates from a cross between Cabernet Franc and Magdeleine Noire des Charentes, have endowed it with a unique versatility and resilience. These traits have not only facilitated its widespread cultivation but also made it a key player in the face of global viticultural challenges, particularly those posed by climate change. Merlot’s early ripening nature and resistance to certain diseases make it an essential cultivar for regions facing increasingly unpredictable weather patterns. In this context, this review aims to highlight the importance of this grape variety by detailing the factors that contribute to its aromatic complexity and sensory appeal, which make Merlot wines are highly appreciated by both consumers and experts due to its balanced aromatic profile. As the wine industry grapples with the effects of climate change and shifting consumer preferences, understanding Merlot’s strengths and potential becomes even more critical. By integrating genetic, agronomic and oenological perspectives, this work emphasizes Merlot’s current significance and highlights its strategic importance for the future of global viticulture.